The perception of spatial relationship in the performance of the effectiveness of the triple jump for beginners ages 13-14 years - Faaq, Hydar (Journal of Physical Education, 2017)
The research aims to find out the relationship between the perception of spatial and learn the effectiveness of triple jump for beginners ages 13-14 years and to find a significant relationship as well have been a brief explanation of each of the sense as well as cognition researcher has used the descriptive approach to relevance nature of the problem to find where the research community are middle school students in Baghdad's Karkh province of (medium Uqba) for Boys was chosen Division random way out (5 people) from the second stage in this school two of them Raspin to this stage and two did not attend During the tests, and thus the total sample (80) student, has undergone the research community of the tests used in the research, namely, (test sense of place and test evaluation of performance skills to the skill of the triple jump) and then were treated statistically in order to know the relationship between research and moral variables Through the relationship Results researcher reached the following conclusions:•Knowledge of the relationship between the perception of spatial learning and the effectiveness of the triple jump for beginnersages13-14years•When teaching the triple jump events for beginnersages13-14years old must pay attention to the spatial perceptionThrough the conclusion reached by their searcher has developed the following recommendations:•Attention to spatial sensory perception when teaching effectiveness of the triple jump for beginner's ages13-14 years